A Review on Aluminum Alloy Recycling Technique - Liaw, Lioyd Leond; Yusuf , Nur Kamilah (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Aluminium are the most often used material on a daily basis and can be frequently recycled without loss of its properties. Aluminium considers as fast-growing in the market because of its physical properties. Therefore, the demand usage of aluminium material will increase as well as the impact to the environment when producing aluminium. So, there are several techniques that currently being used by the industry to recycle the aluminium which are conventional recycling, semi-direct recycling, and direct recycling. Thus, this paper presents a review on the techniques used in recycling aluminium as well as responses analyzed in collected research paper and discuss the benefits obtained from the techniques used. Moreover, this paper is categories as a theoretical literature review. So, this paper involves 2 main step which are surveying and critically reading the existing literature and also summarizing and taking the point of the analysis in an ordered manner. Then, the historical trend can show that the conventional recycling becoming less attractive compare semi direct and direct recycling because both recycling are much more eco-friendly and less energy usage as well as low cost operation. However, more study should be done on this topic frequently so that a better review and understanding on this topic can be obtain.